One size does not fit all: Factors associated with increased frequency of radiation overexposure alerts based on fixed-alert thresholds. (February 2021) - Valtchinov, Vladimir I.; Siegelman, Jenifer; Zhai, Bingxue K.; Khorasani, Ramin; Sodickson, Aaron
Highlights: Our study defines key determinants of radiation dose alert frequency and limitations of size-agnostic alert thresholds. The frequency of CT dose alerts derived from comparison with fixed threshold values were driven heavily by patient factors. Fixed thresholds create non-actionable alerts in big patients, and missed to identify high-dose outliers in small patients. Abstract: Objectives: Quantify the expected rate of CT radiation dose alerts for three body regions using accepted radiation dose benchmarks and assess key determinants of alert frequency. Methods: This IRB-approved retrospective cohort study evaluated consecutive CT examinations performed between July and December 2013 within an academic medical system. CTDIvol x-ray tube output metrics were compared to the body-region-specific benchmark levels, Achievable Doses (AD), Diagnostic Reference Levels (DRL), and Dose Notification Values (DNV). A logistic regression model for the simulated alerts was fit as a function of the independent predictors: scanner, body region, gender, weight, and age. Results: For 17, 000 exams, the proportion of events triggering alerts increased with patient weight. Significant covariates were scanner, body region, patient weight and patient age (all p < 0.0001). Odds of alert generation for the AD, DRL, and DNV benchmarks increased by 7.6%, 6.6% and 2.9% per kilogram, respectively, and by 0.8%, 1.1% and −2.7% per year of age (all p < 0.0001). Compared to the most highly optimized scanner, odds of alert generation varied by a factor of 595 for AD, 1126 for DRL, and 13 for DNV. Conclusion: Alert frequency was significantly correlated with weight, age, body region and scanner. Controllable factors include scanner functionality and associated protocol optimization. Patient factors driving alert frequency are predominantly weight, and to a lesser degree, age. Size-agnostic fixed dose thresholds can frequently produce false positive alerts in appropriately performed exams of large patients, while missing opportunities to identify outlier scans of higher-than-expected dose in small patients.